2004
DOI: 10.1128/mcb.24.6.2467-2477.2004
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Specificity of Xenopus TFIIIA for Transcription of Somatic 5S rRNA Genes

Abstract: Xenopus transcription factor IIIA (TFIIIA) is phosphorylated on serine-16 by CK2. Replacements with alanine or glutamic acid were made at this position in order to address the question of whether phosphorylation possibly influences the function of this factor. Neither substitution has an effect on the DNA or RNA binding activity of TFIIIA. The wild-type factor and the alanine variant activate transcription of somatic-and oocyte-type 5S rRNA genes in nuclear extract immunodepleted of endogenous TFIIIA. The glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
2
6
0
Order By: Relevance
“…Indeed, in a recent paper describing a study 165 of the sea urchin P. lividus, we demonstrated not only that all clusters are 166 transcribed, but also that the 700 bp cluster exhibited a high level of 167 heterogeneity in terms of sequence [25]. We also demonstrated that a 168 regulation exists during the developmental stage and in adult tissue, 169 as reported in Xenopus laevis [31][32][33][34]. In this organism, in particular, ants are substituted by somatic-specific ones.…”
supporting
confidence: 70%
“…Indeed, in a recent paper describing a study 165 of the sea urchin P. lividus, we demonstrated not only that all clusters are 166 transcribed, but also that the 700 bp cluster exhibited a high level of 167 heterogeneity in terms of sequence [25]. We also demonstrated that a 168 regulation exists during the developmental stage and in adult tissue, 169 as reported in Xenopus laevis [31][32][33][34]. In this organism, in particular, ants are substituted by somatic-specific ones.…”
supporting
confidence: 70%
“…Consistent with this position of the amino acid, we found no evidence that phosphorylation of TFIIIA affects its binding affinity for the promoters of either the oocyte-or somatic-type genes nor for 5 S rRNA, suggesting that the functional effect of modification likely alters an interaction with another protein (24). To address this question, we carried out a yeast two-hybrid screen of a Xenopus expression library using the first four fingers of TFIIIA as bait and identified PIAS2b, a SUMO ligase, and XCtBP, a transcriptional corepressor regulated by SUMOylation, as candidates.…”
supporting
confidence: 67%
“…Substitution with glutamic acid at this position serves as a putative phosphomimetic that cannot support transcription of the oocyte-type genes in vitro or in vivo despite binding and recruiting at least one other polymerase III transcription factor (24). This observation suggests that this region of TFIIIA is involved in an interaction that regulates the differential transcription of 5 S rRNA genes.…”
Section: Pias2 and Xctbp Bind To The N Terminus Of Tfiiia-serinementioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of histone H1 into chromatin during Xenopus embryogenesis directs the specific repression of the TFIIIA-activated transcription of 5S rRNA genes (Bouvet et al 1994). Phospho-form of TFIIIA may allow the factor to act as repressor for oocyte-type 5S rRNA genes (Ghose et al 2004). TFIIIA favorably binds to the somatic nucleosome whereas H1 preferentially binds to the oocyte nucleosome, excluding TFIIIA binding in Xenopus oocyte (Panetta et al 1998).…”
Section: Transcription Factor Iiiamentioning
confidence: 99%